2003
DOI: 10.1152/japplphysiol.00594.2003
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific effects of thyroid hormones on cardiopulmonary function in SHHF rats

Abstract: der-specific effects of thyroid hormones on cardiopulmonary function in SHHF rats. J Appl Physiol 95: 2292-2298, 2003. First published August 8, 2003 10.1152/japplphysiol. 00594.2003.-Spontaneously hypertensive heart failure (SHHF) rats develop hypertension and heart failure. We hypothesized that induction of hyperthyroidism should accelerate development of heart failure in male SHHF rats. Male and female SHHF rats received diets containing desiccated thyroid glands (DTG) or a control diet for 8 wk. Male and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Longitudinal studies indicated that mutant mice homozygote (ob/ob) for the obesity gene also developed rapid baseline breathing relative to wild-type mice (31,35,46). Further evidence for obesity, and not predominantly hypertension, contributing to the higher f and lower VT pattern in DI-treated obese SHHF rats in the present study comes from a recent study of lean SHHF rats (40). Male lean SHHF in that study exhibited hypertension and had a f of 111 Ϯ 3 breaths/ min relative to 115 Ϯ 2 breaths/min in Wistar-Kyoto normotensive control rats.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Longitudinal studies indicated that mutant mice homozygote (ob/ob) for the obesity gene also developed rapid baseline breathing relative to wild-type mice (31,35,46). Further evidence for obesity, and not predominantly hypertension, contributing to the higher f and lower VT pattern in DI-treated obese SHHF rats in the present study comes from a recent study of lean SHHF rats (40). Male lean SHHF in that study exhibited hypertension and had a f of 111 Ϯ 3 breaths/ min relative to 115 Ϯ 2 breaths/min in Wistar-Kyoto normotensive control rats.…”
Section: Discussionsupporting
confidence: 51%
“…After the rat became accustomed to his surroundings and frequency of breathing (f; breaths/min) stabilized, ventilation was evaluated using the barometric method used frequently in our laboratory (40). The Bio-Pac acquisition computer system was used to record the breathing pattern of each rat to determine f and tidal volume (VT) and calculate minute ventilation (V E), the product of the two previous variables.…”
mentioning
confidence: 99%
“…Hamsters were placed into a cylindrical Plexiglas chamber for measurement of oxygen consumption as described previously (28). Oxygen consumption was corrected to STPD values and divided by body weight.…”
Section: Methodsmentioning
confidence: 99%
“…Studies that investigated the interaction between hypertension, gender and respiratory control have mainly focused on sleep apnea syndrome (7), and male gender and hypertension have been suggested to be risks for human sleep apnea (8). Animal models have been useful to investigate the relationship between hypertension and abnormal control of breathing (9). Despite recent literature reviews focusing on the relationship between breathing and hypertension (10,11), a possible relationship between hypertension and abnormal ventilatory control was never examined before in spontaneously hypertensive rats (SHR), an outstanding hypertensive model.…”
Section: Introductionmentioning
confidence: 99%